2018
DOI: 10.46989/001c.20907
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation of Glycyrrhetinic Acid (GA) Promoting Lipid Lipolysis from Blunt Snout Bream Megalobrama amblycephala by TNF-α and LPL Expression

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) has been published exclusively as an online Open Access scientific journal, accessible by all. Please visit our IJA Website http://www.aquaculturehub.org/group/israelijournalofaquaculturebamidgehija for free publications and to enable you to submit your manuscripts. This transformation from a subscription printed version to an online Open Access journal aims at supporting the concept that scientific peer-reviewed publications and thus the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In this study, the supplementation of 0.02% GL could decrease the mRNA expression of proinflammatory factors ( il-1β and il-6 ) and increase the mRNA expression of anti-inflammatory factor ( il-10 ), which probably due to the higher proportion of GL supplementation could better reflect the anti-inflammatory capacity of GL. Similar results have been confirmed in studies of silver carp [ 24 ], Asian seabass [ 21 ], blunt snout bream [ 22 ], and yellow catfish [ 41 ]. In summary, the supplementation of 0.02% GL could alleviate the inflammation of large yellow croaker larvae.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, the supplementation of 0.02% GL could decrease the mRNA expression of proinflammatory factors ( il-1β and il-6 ) and increase the mRNA expression of anti-inflammatory factor ( il-10 ), which probably due to the higher proportion of GL supplementation could better reflect the anti-inflammatory capacity of GL. Similar results have been confirmed in studies of silver carp [ 24 ], Asian seabass [ 21 ], blunt snout bream [ 22 ], and yellow catfish [ 41 ]. In summary, the supplementation of 0.02% GL could alleviate the inflammation of large yellow croaker larvae.…”
Section: Discussionsupporting
confidence: 83%
“…However, the application of GL in aquatic diets has been rarely reported. Results of the study in white shrimp (Litopenaeus vannamei), Asian seabass (Lateolabrax maculatus), and blunt snout bream (Megalobrama amblycephala) prove that GL could improve the anti-inflammatory capacity [21][22][23]. In particular, Harikrishnan et al found that different dosages of GL could improve the growth, activity of digestive-antioxidant, and innate-adaptive defense of silver carp (Hypophthalmichthys molitrix) [24].…”
Section: Introductionmentioning
confidence: 97%